A genetic system for Citrus Tristeza Virus using the non-natural host Nicotiana benthamiana: an update - Ambrós, Silvia; Ruiz-Ruiz, Susana; Peña, Leandro; Moreno, Pedro; Moreno, Pedro (Frontiers in Microbiology, 2013)
In nature Citrus tristeza virus (CTV), genus Closterovirus, infects only the phloem cells of species of Citrus and related genera. Finding that the CTV T36 strain replicated in Nicotiana benthamiana (NB) protoplasts and produced normal virions allowed development of the first genetic system based on protoplast transfection with RNA transcribed from a full-genome cDNA clone, a laborious and uncertain system requiring several months for each experiment. We developed a more efficient system based on agroinfiltration of NB leaves with CTV-T36-based binary plasmids, which caused systemic infection in this non-natural host within a few weeks yielding in the upper leaves enough CTV virions to readily infect citrus by slash inoculation. Stem agroinoculation of citrus and NB plants with oncogenic strains of Agrobacterium tumefaciens carrying a CTV-T36 binary vector with a GUS marker, induced GUS positive galls in both species. However, while most NB tumours were CTV positive and many plants became systemically infected, no coat protein or viral RNA was detected in citrus tumours, even though CTV cDNA was readily detected by PCR in the same galls. This finding suggests i) strong silencing or CTV RNA processing in transformed cells impairing infection progress, and ii) the need for using NB as an intermediate host in the genetic system. To maintain CTV-T36 in NB or assay other CTV genotypes in this host, we also tried to graft-transmit the virus from infected to healthy NB, or to mechanically inoculate NB leaves with virion extracts. While these trials were mostly unsuccessful on non-treated NB plants, agroinfiltration with silencing suppressors enabled for the first time infecting NB plants by side-grafting and by mechanical inoculation with virions, indicating that previous failure to infect NB was likely due to virus silencing in early infection steps. Using NB as a CTV host provides new possibilities to study virus-host interactions with a simple and reliable system.